Compensation Management for Improving Teacher Work Quality - Ariyana Luthfiyani, Dewi; Sumaryanto Florentinus, Totok; Yulianto, Arief (Educational Management, 2021)
Abstrak The purpose of this study was to describe and analyze the initial planning of compensation management at SMA N 1 Mayong Jepara. This research approach is a qualitative approach with a explorative case study design. Data collection was carried out by observation, interviews, and documentation by eight participants which included the principal, six teachers and an education staff. The results of this study indicate that the initial planning of compensation management at SMA N 1 Mayong Jepara is (1) planning compensation management objectives, where the main purpose of compensation management planning is for the welfare of teachers and education staff. (2) planning a compensation management strategy, where the specific compensation management strategy is to build a work culture of MEJENG SEKSI to achieve school goals so that teachers and education staff improve work quality. The benefit of this research is to provide insight into management related education compensation management planning in improving the quality of teacher work at the high school level and used as a reference and evaluation materials evaluation material in improving the quality of teacher work. Kata Kunci: Manajemen Kompensasi, Kualitas Kerja